EFFECTS OF DIETARY INTERVENTION ON LIPIDS PROFILE OF HIV INFECTED PATIENTS ON ANTIRETROVIRAL TREATMENT (ART) - Sonia Maria de Figueiredo; Maria Goretti Moreira Guimaraes Penido; Milena Maria Moreira Guimaraes; Lucas Jose de Campos Machado; Sidney Augusto Vieira Filho; Maria Arlene Fausto; Carlos Mauricio de Figueiredo Antunes; Rachel Basques Caligiorne; Dirceu Bartolomeu Greco (European Scientific Journal, ESJ, 2013)
The aim of this study was to evaluate the effects of dietary intervention on serum lipids, saturated fatty acids and trans-fatty acids in HIV-infected individuals on ART. This design was a non-randomized, non-controlled nutrition intervention study. The setting was in Referral Center in Infectious and Parasitic Diseases. Subjects: 57 HIV-infected patients, aged 28.4–68.4 years, were recruited from the outpatient clinic of a reference center. Clinical and ﻿﻿biochemical data were collected from all before and after nutritional counseling. The majority of patients were male, with at least 8 years of schooling and 38.5% had BMI ≥ 25 kg/m2. Forty-eight (84%) patients had a family history of chronic diseases and the most common were coronary events (50%). All patients were exposed to antiretroviral therapy and 51% were using Protease Inhibitor. Twelve patients (21%) had a very low HDL-cholesterol and 26 patients (45.5%) had hypertriglyceridemia. There were a significant increase in carbohydrate (p=0.02), protein (p=0.04), selenium (p<0.00005), and calcium (P=0.0007) intake and a significant decreased in total lipid (p=0.002), saturated fatty acids (p=0.0004), trans fatty acids (p=0.0005), and cholesterol total (p=0.0004) after dietary intervention. No significant difference was observed in energy, total fiber, polyunsaturated fatty acids and monounsaturated fatty acids after dietary intervention. This study suggested an efficacy of nutritional intervention in the prevention of changes in lipid profile of HIV-positive individuals on ART. These findings also suggest that nutritional intervention should be considered for all patients on ART.